Retrospective Analysis of Emergency Thoracotomy Outcomes in Patients with Blunt versus Penetrating Thoracic Trauma: A Comparative Study from a Tertiary Care Center (POF Hospital Wah Cantt) - SHAHID, ABDUL REHMAN; KABIR, MALIK MUHAMMAD; KHAN, MUHAMMAD WALLEED; REHAN, ARIBA; AKRAM, MUHAMMAD; HASSAN, MUHAMMAD (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Thoracic trauma is a major contributor to morbidity and mortality worldwide. Emergency thoracotomy (ET) is a critical, life-saving intervention for patients with severe chest trauma, but outcomes differ significantly depending on the mechanism of injuryblunt versus penetrating. This study retrospectively analyzes and compares the outcomes of ET performed at POF Hospital Wah Cantt. Objective: To compare the clinical outcomes of emergency thoracotomy in patients with blunt versus penetrating thoracic injuries. Methods: A retrospective study was conducted on patients who underwent emergency thoracotomy for chest trauma at POF Hospital Wah Cantt between January 2018 and December 2023. Patients were divided into two groups based on trauma type: blunt (Group A) and penetrating (Group B). Demographics, indications, intraoperative findings, complications, ICU stay, and survival rates were analyzed. Results: A total of 62 patients were included (blunt: 28, penetrating: 34). The survival rate in Group B (penetrating) was significantly higher (41.2%) compared to Group A (21.4%). Blunt trauma cases had higher incidence of multi-organ injury and required prolonged ICU care. Common indications for ET were massive hemothorax, cardiac tamponade, and major vessel injury. Conclusion: Penetrating thoracic injuries are more likely to benefit from emergency thoracotomy compared to blunt injuries. Mechanism of trauma should guide ET decisions. Early identification and surgical intervention, especially in penetrating injuries, can improve survival.